Through An Equity Lens: Illuminating The Relationships Among Social Inequities, Stigma And Discrimination, And Patient Experiences of Emergency Health Care. (April 2022) - Varcoe, Colleen; Browne, Annette J.; Bungay, Vicky; Perrin, Nancy; Wilson, Erin; Wathen, C. Nadine; Byres, David; Roberta Price, Elder
People who experience the greatest social inequities often have poor experiences in emergency departments (EDs) so that they are deterred from seeking care, leave without care complete, receive inadequate care, and/or return repeatedly for unresolved problems. However, efforts to measure and monitor experiences of care rarely capture the experiences of people facing the greatest inequities, experiences of discrimination, or relationships among these variables. This analysis examined how patients' experiences, including self-reported ratings of care, experiences of discrimination, and repeat visits vary with social and economic circumstances. Every consecutive person presenting to three diverse EDs was invited if/when they were able to consent; 2424 provided demographic and contact information; and 1692 (70%) completed the survey. Latent class analysis (LCA) using sociodemographic variables: age, gender, financial strain, employment, housing stability, English as first language, born in Canada, and Indigenous identity, indicated a six-class solution. Classes differed significantly on having regular access to primary care, reasons for the visit, and acuity. Classes also differed on self-reported discrimination every day and during their ED visit, ratings of ED care, and number of ED visits within the past six months. ED care can be improved through attention to how intersecting forms of structural disadvantage and inequities affect patient experiences.